Ecological terminology: The term "use of natural resources " in Russian texts of various registers - K. Kovács, Krisztina (Slavica, 2025)
The relevance of this paper stems from the rapid development of ecological knowledge, accompanied by the active formation and integration of new specialized terminology. Due to a growing interest in issues of applied ecology, sustainable development, and rational use of natural resources, ecological vocabulary is steadily expanding and becoming established in texts of various genres and functional styles. This dynamism necessitates a linguistic analysis of word formation of new terminology and the use of specialized vocabulary in the context of the environment. The paper examines the specifics of how the term prirodopol'zovanie “use of natural resources” functions in Russian-language texts representing different functional styles such as scientific, official-administrative, and journalistic texts.